ELECTIONS AND HUMAN SECURITY IN NIGERIA: A REFLECTION OF THE 2019 GENERAL ELECTIONS AND THE WAY FORWARD - Nwambuko, Temple C.; David, Aniefiok Titus; Osuafor, Joy Nwakaego (African Journal of Social and Behavioural Sciences, 2024)
This paper examined elections and human security in Nigeria with reference to the 2019 general elections. In Nigeria, there are manifold human security challenges before, during and after general elections. This is rooted deep within the fabric of the state (government security structures such as the police) or state mechanisms/actors (militant and terrorist groups) competing and overlapping each other. The lack of meaningful progress in addressing the prevalent political violence, lack of accountability for human rights abuses and the inability of security forces to respond effectively to threats to people’s lives and security affected the way and manner in which the 2019 general elections were conducted in the country. Therefore, this study aimed to determine how general elections were conducted and how they grossly affected human security in Nigeria. To achieve this goal, the paper adopted the qualitative descriptive research design; relied on secondary data; applied social contract theory; and theoretically analysed the collected data. This study revealed that the nefarious activities of political parties, unpatriotic politicians, terrorism threats and their similarities in Nigeria, to a large extent, undermined the level of human security before, during and after the 2019 general elections in the country; and that the factors militating against human security during the 2019 general elections were security issues, partisanship among security forces, vote rigging, vote-buying, fake news etc. This study recommended. among others, the need for improved security surveillance, vigilance and high-level intelligence gathering by military and para-military agencies in Nigeria.